Challenges and paradigm of national and international security of the XXI century: economic and technogenic discourse - Oksana Chernega; Yuliia Bocharova (PC TECHNOLOGY CENTER, 2022)
The interdisciplinarity, multidimensionality and complexity of the security paradigm in the XXI century are reflected. Theoretical and applied (practical) aspects of ensuring the security of objects of global, sub-global, macro-, meso- and micro-levels of security in the conditions of an unprecedented transformation of the world, an increase in the level of turbulence and uncertainty recorded in the global and national contexts of development, the latest challenges, opportunities and threats at the beginning of the XXI century. The development of theoretical aspects of ensuring security has found manifestation in: identification of approaches to understanding the essence of the concept of "security", security paradigms, object-subject, sectoral structure, analytical levels of security; substantiation and presentation of the author's approaches to understanding the essence of the concepts of "national security", "public administration in the field of security", "financial security", "financial security of sustainable development", "economic security", "security and protection in global tourism", "security enterprises", incl. "economic security of the enterprise"; allocation of components and indicators of national security, incl. national financial and economic security, economic security of enterprises, industries, innovative ecosystems; determining the meaning and role of language and linguistic identity, development of innovative ecosystems, financial and economic security, enterprise security to ensure national security; determining the importance and role of national security and its components, financial security of sustainable development, tourism security to ensure personal and global security; improving the classification of international financial resources involved in the field of sustainable development, identifying measures to ensure the financial security of sustainable development at different levels of management; identification of models for ensuring the security of states and their features; substantiation of the architecture of the intellectual control system of food industry enterprises. The development of practical aspects of ensuring security has found expression in: the identification of global threats to national security in the XXI century, the vector of their transformation, the time lag of manifestation and the degree of influence; sound configuration of global financial security of sustainable development, measures to ensure financial security of sustainable development at different levels of government; development of a model for predicting the emergence of threats to the financial condition of Ukraine, a system of corrective measures of economic policy on the part of macroeconomic regulation bodies in order to stop the inertial development of the forecast situation to ensure the financial security of the state; assessment by the taxonomy method of the integral indicator of the economic security of the EU countries; construction of a matrix of transitions of the EU countries between the states of economic security of the pre-covid and covid-periods; building a security profile for Ukraine and the EU; forecasting the losses of the EU countries from military operations on the territory of Ukraine; identification of security parameters and efficiency markers of innovative ecosystems; identification of the state and features of the development of innovative ecosystems of the leading countries of innovative development; determining the 10 most and least safe and reliable countries in the world for travel; building a map of the distribution of countries in the world according to the Global Peace Index; determination of the current state and features of the development of hotel and restaurant enterprises in Ukraine; calculation and interpretation of the integral indicator of economic security of hotel and restaurant enterprises using the taxonomy method for 2015-2020; substantiation of the strategy for ensuring the economic security of hotel and restaurant enterprises and management decisions for its implementation for the future period; development of mathematical models for the processes of preparation and improvement of water quality indicators, preparation and dosage of flour, preparation of bread starter, dough, dispersion for dough of functional applications, proofing and baking processes using ultrasonic monitoring and intensification systems; designing local adaptive control systems for relevant processes; substantiation of modern features of intelligent control of complex technological processes for the production of bakery products with digital control algorithms for food industry enterprises in the territories of technogenic load.
Keywords: 320; Security; Security paradigm; National security; Public administration in the field of security; Threats; Risks; National identity; Language identity; Financial security of the state; Economic security of the state; Economic security of the enterprise; Global financial security of sustainable development; Security indicators